Probiotics [LGG-BB12 or RC14-GR1] versus placebo as prophylaxis for urinary tract infection in persons with spinal cord injury [ProSCIUTTU]: a study protocol for a randomised controlled trial. Issue 1 (December 2016) - Lee, Bonsan; Toh, Swee-Ling; Ryan, Suzanne; Simpson, Judy; Clezy, Kate; Bossa, Laetitia; Rice, Scott; Marial, Obaydullah; Weber, Gerard; Kaur, Jasbeer; Boswell-Ruys, Claire; Goodall, Stephen; et al.
Abstract Background Urinary tract infections [UTIs] are very common in people with Spinal Cord Injury [SCI]. UTIs are increasingly difficult and expensive to treat as the organisms that cause them become more antibiotic resistant. Among the SCI population, there is a high rate of multi-resistant organism [MRO] colonisation. Non-antibiotic prevention strategies are needed to prevent UTI without increasing resistance. Probiotics have been reported to be beneficial in preventing UTIs in post-menopausal women in severalin vivo andin vitro studies. The main aim of this study is to determine whether probiotic therapy with combinations of Lactobacillus reuteri RC-14 + Lactobacillus rhamnosus GR-1 [RC14-GR1] and/or Lactobacillus rhamnosus GG + Bifidobacterium BB-12 [LGG-BB12] are effective in preventing UTI in people with SCI compared to placebo. Method This is a multi-site randomised double-blind double-dummy placebo-controlled factorial design study conducted in New South Wales, Australia. All participants have a neurogenic bladder as a result of spinal injury. Recruitment started in April 2011. Participants are randomised to one of four arms, designed for factorial analysis of LGG-BB12 and/or RC14-GR1 v Placebo. This involves 24 weeks of daily oral treatment with RC14-GR1 + LGG-BB12, RC14-GR1 + placebo, LGG-BB12 + placebo or two placebo capsules. Randomisation is stratified by bladder management type and inpatient status. Participants are assessed at baseline, three months and six months for Short Form Health Survey [SF-36], microbiological swabs of rectum, nose and groin; urine culture and urinary catheters for subjects with indwelling catheters. A bowel questionnaire is administered at baseline and three months to assess effect of probiotics on bowel function. The primary outcome is time from randomisation to occurrence of symptomatic UTI. The secondary outcomes are change of MRO status and bowel function, quality of life and cost-effectiveness of probiotics in persons with SCI. The primary outcome will be analysed using survival analysis of factorial groups, with Cox regression modelling to test the effect of each treatment while allowing for the other, assuming no interaction effect. Hazard ratios and Kaplan-Meier survival curves will be used to summarise results. Discussion If these probiotics are shown to be effective in preventing UTI and MRO colonisation, they would be a very attractive alternative for UTI prophylaxis and for combating the increasing rate of antibiotic resistance after SCI. Trial registration Australian New Zealand Clinical Trials Registry [ACTRN 12610000512022 ]. Date of registration: 21 June 2010.